Mengembangkan Kemampuan Sosial Anak Usia 5-6 Tahun Melalui Permainan Tradisional Ular Naga Di KB Qolbu Lebai Sandar Tahun 2021 - Muazar Habibi; Nurhasanah Nurhasanah; Ika Rachmayani; Nurul Aini (Indonesian Publication Center, 2022)
The purpose of research to expand child social skill 5-6 years old start from playing snak dragon traditional at KB Qolbu Lebai start from playing dragon snake at KB Qolbu Lebai Sandar.kind of this research is subjeck development research, this reaserch is group B consists of 8 children’data collection techniq in research using observation techniq, data analysis tekhniq using quantitative analysis. This research uses descriptive qualitative research. There are 5 steps in this traditional dragon snake game, namely: (1) children who act as dragons line up neatly to the back and children who act as parents stand at the front as carriages (2) then the dragon snakes around the mother while singing the dragon song (3) after the song is finished singing maa one child is caught inside carriage (4) after that, then the mother negotiates about her child being caught after that she chooses the mother and stands behind the mother and then the song is sung again until the dragon is finished. (5) after finish so the mather have the least child wiil be catch most tail until tail caught so the game is finish the playing. The reaserch shows that was the stage of development I reached 29,50% while in development II began to see an increased percentage 37,8% and enhanced optimally at the III stage of development with percentage 56,87% based on the research can make conclution that with the traditional game of dragon snake in development with step by step right up to can increase the social capacities 0f 5-6 year old children at di Kb Qolbu Lebai Sandar year 2021.